Assessing positive and negative factors as catalysts for enhancing European food security amidst threats to SDG 2 - Mohammad Fazle Rabbi; Sándor Kovács; József Popp; Veronika Fenyves (Sustainable Futures)
Food security remains a critical challenge for the European Union (EU) in achieving Sustainable Development Goal 2 (Zero Hunger). Despite extensive research, three key gaps persist: (1) limited understanding of how positive and negative factors interact to shape food security outcomes; (2) insufficient evidence on the mediating mechanisms linking these factors to SDG-2 achievement; and (3) inadequate quantification of country-specific vulnerabilities within perceived food insecurity. This study addresses these gaps by analysing the combined influence of positive factors, such as GDP growth, agricultural investment, and access to safe water and sanitation, alongside negative factors like cereal import dependency, food price inflation, and nutritional imbalances. SEM results reveal GDP growth as a strong positive driver of food security (path coefficient = 0.845), while cereal import dependency (path coefficient = -0.709) and food price inflation (path coefficient = -0.697) exacerbate vulnerabilities. Austria and The Netherlands exhibit high food security levels due to robust GDP growth rates (5.0 % and 4.8 %, respectively), while Hungary and Slovakia face affordability challenges due to slower GDP growth (2.5 % and 2.3 %) and high food price anomalies (+2.7 % CPI deviation). Nutritional imbalances persist across the region, with obesity rates reaching 25.4 % in Hungary and undernourishment peaking at 4.9 % in Slovakia. Agricultural investment emerges as a critical enabler for domestic production (highest score in Czechia: 2.5), while cereal import dependency negatively impacts countries like The Netherlands (dependency rate: 90.3 %). These findings emphasize the need for targeted interventions, including agricultural investment, food sourcing diversification, price stabilization measures, social safety nets, and infrastructure development to enhance resilience and achieve SDG-2.